Development of a descriptive study of work stress, physical activity, eating habits and obesity in the maquiladora industry using software applications - Armenta, Oziely; Maldonado-Macías, Aide Aracely; Hernandez Arellano, Juan Luis; Baez, Yolanda (2020)
Workers around the world face major changes in work organization and industrial relations to fulfill the demands of modern working life. The problem of work stress and obesity have become rather delicate subjects because of the negative consequences it brings for employees and companies. The objectives of this research are perform a descriptive analysis using the SPSS v.23 software on work stress, physical activity, eating habits and obesity in the industry for sample characterization.